A Self-Assessment Guide for Health Care Organizations : Quality, Safety, Ethics - International Finance Corporation (Washington, DC, 2015)
This guide is designed to assist health care organizations in emerging markets to reach ‘international standards’ of quality and patient safety. It will enable them to conduct an organizational self-assessment to identify how well they are meeting defined standards in five key areas: governance and leadership, ethics and patient rights, quality measurement and improvement, patient safety, and facility safety and emergency management. The guide will help them to gauge how much effort they need to make, and in which areas, to reach international standards. The assessment is not, in itself, intended for use as an accreditation tool, although it is likely to be a useful tool for organizations that are actively considering international accreditation. If the organization has already attained international accreditation, the Guide may serve to reinforce its commitment to the process of continual improvement. The document provides information regarding key principles underlying quality improvement initiatives. And it guides users through the important steps of undertaking a quality self-assessment. These include: getting organized, collecting data, identifying gaps and developing plans for meeting key standards.